Questionnaire for Eudaimonic Well-Being: Psychometric Validation Among Malaysian Youth - A. Malek, Mohd Ahsani; Saad, Nurulwahida; Mohd. Hoesni, Suzana; Ibrahim, Muhamad Ariff; Adi, Nurul Shafira; Mohd Nazori, Mohd Nazir (Makara Journal of Health Research, 2026)
Background: The rising prevalence of mental illness underscores the need to understand how individuals can live and flourish under such conditions. In Malaysia, research has largely emphasized diagnosis and treatment, with limited focus on positive psychology and few validated instruments. This study aimed to translate and validate the questionnaire for eudaimonic well-being (QEWB) among Malaysian youth. Methods: The QEWB was translated into Malay using back-to-back translation and administered to undergraduates from four public universities through a cross-sectional survey design. Convenience quota sampling was used, resulting in 229 respondents completing the online form to measure sociodemographic characteristics, eudaimonic well-being, stress, and general well-being. Factor analyses were used to assess construct validity, whereas Pearson’s correlation was used to test criterion validity. Results: A three-factor (17 items) and one-factor (15 items) model were supported. The 3 factors—intensity of self-expression, importance of fulfillment, and attitude toward growth—showed good validity and reliability (α = 0.74 – 0.88). The one-factor model also exhibited strong validity and reliability (α = 0.81). Both models significantly correlate positively with general well-being (r = 0.44 – 0.76, p < 0.01) and negatively with stress (r = −0.29 to −0.43, p < 0.01). Conclusions: The Malay QEWB is reliable and facilitates the integration of eudaimonic well-being in Malaysian research and practice.